Distribución espacial de la población en la Zona Metropolitana de la Ciudad de México, 1950-1990 - Garrocho, Carlos (El Colegio de México A.C., 1996)
This study explores how the spatial distribution of population in the Metropolitan Area of Mexico City (MAMC) has changed between 1950 and 1990. First of all it presents the structural concepts of this research, and then analyzes the growth and spatial distribution of the MAMC population, surveying the city from three analytical viewpoints: as a point (to detect absolute demographic changes), as an axis (to explore changes in population density and concentration and spatial aspects of home location), and as an area (to estimate the spatial differences of demographic change, outline density variation patterns on a bi-dimensional space, and identify MAM'S many-centered structure). Several techniques of spatial analysis were applied throughout this work; two of them are relatively new in Mexican literature on urban population (the Wright index and the analysis of spatial auto correlation) and another is a contribution of this study (the index of density primacy of intra-urban population). The results of this study indicate that MAMC: i) continues to decrease in its central areas, ii) presents a process of home location with expanding waves and moments of consolidation, iii) has a many-centered metropolitan structure, and iv) the dominating center separates progressively from the traditional center and is already located in the State of Mexico.